The little SAS book for Enterprise Guide 4.1 - Slaughter, Susan J. (SAS Institute, 2006)
Learning to use SAS Enterprise Guide has never been easier! With The Little SAS Book for Enterprise Guide 4.1, Susan Slaughter and Lora Delwiche help you quickly become familiar with the SAS Enterprise Guide point-and-click environment. A series of carefully designed tutorials help you master the basics of the tasks you will want to do most frequently. The reference section of the book expands on the tutorial topics, focusing on specific features. If you are new to SAS or new to SAS Enterprise Guide, this book will be an invaluable tool on your way to becoming an expert.